2020
DOI: 10.1038/s41598-019-57057-8
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic-F127/Platelet Microvesicles nanocomplex delivers stem cells in high doses to the bone marrow and confers post-irradiation survival

Abstract: Platelet microvesicles (pMVs) are submicron-sized heterogeneous vesicles released upon activation and contain several membrane receptors and proteins (CD41, CD61, CD62, CXCR4, PAR-1, etc.). We have revealed their ability to adhere to the triblock copolymer pluronic-F127 (PF127) and form a platelet microvesicular nanocloud which has the potential to enhance the transvascular migration of hematopoietic stem cells across the sinusoidal endothelium to the bone marrow. Besides, the pMVs nanoclouds bestow survival b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…More recently, Chander and Gangenahalli revealed that complexes between pMVs and pluronics form “nanoclouds” that cover single HSCs and increase the migration of HSCs across sinusoidal ECs to the BM ( Chander and Gangenahalli, 2020b ). Pluronics represent a group of thermoreversible copolymers which can firmly associate with pMVs ( Zhong et al, 2018 ) and have been frequently used for drug delivery approaches.…”
Section: The Bone Marrow Niche and Hematopoietic Stem Cell Homingmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Chander and Gangenahalli revealed that complexes between pMVs and pluronics form “nanoclouds” that cover single HSCs and increase the migration of HSCs across sinusoidal ECs to the BM ( Chander and Gangenahalli, 2020b ). Pluronics represent a group of thermoreversible copolymers which can firmly associate with pMVs ( Zhong et al, 2018 ) and have been frequently used for drug delivery approaches.…”
Section: The Bone Marrow Niche and Hematopoietic Stem Cell Homingmentioning
confidence: 99%
“…In a study from the early 90s, coating of polystyrene NPs with Pluronic F-127 directed more than 50% of intravenously infused polystyrene NPs to the BM ( Porter et al, 1992 ). Loading of HSCs with pMV nanoclouds, in particularly with PF127-stabilized chitosan-alginate, prior to transplantation into lethally irradiated mice led to a 10-fold increase in homing, and effective engraftment and regeneration of the blood lineages ( Chander and Gangenahalli, 2020b ).…”
Section: The Bone Marrow Niche and Hematopoietic Stem Cell Homingmentioning
confidence: 99%
“…Pluronic F127 is a hydrophilic, nontoxic copolymer that is widely used as a pharmaceutical excipient. Biocompatibility, bioadhesion, adaptability, thermosensitivity, and ability to stabilize and protect cargo have all promoted the use of Pluronic F127 as a component in many therapeutic modalities, including nanogels or nanocontainers, microvesicle nancompexes, and engineered tissues [57][58][59][60][61][62]. In these alginate nanoparticles, Pluronic F127 was used as a matrix-stabilizing agent that permits sustained drug release.…”
Section: Formulation Of the Nanoparticles: Overview And Detailed Proceduresmentioning
confidence: 99%
“…The term Pluronic Âź (also known as Poloxamer) identifies a generic block copolymer made up of two units of poly(ethylene glycol) (PEG), separated by a central poly(propylene oxide) unit (PPO). One of the different varieties of Pluronic Âź is the F127 (Figure 1b), which is commercially available due to its physiological properties of low toxicity and high biocompatibility [14]. Furthermore, it displays a double behaviour.…”
Section: Introductionmentioning
confidence: 99%